Not my usual trip: Tide-hailing characterization in Mexico City - Orlando Sabogal-Cardona; Lynn Scholl; Daniel Oviedo; Amado Crotte; Felipe Bedoya (Inter-American Development Bank (IDB), 2021)
The literature on ride-hailing has experienced rapid growth in recent years, with an accent on industrialized cities, mainly in the United States and Europe. Previous research has identified the characteristics and preferences of ride-hailing adopters in a handful of cities. However, given their marked geographical focus, whether such findings are relevant and applicable to the practice of transport planning and regulation in cities in the Global South remains largely untested. This paper examines ride-hailing in the Metropolitan Area of Mexico City. We build on statistical modelling informed by the Mexico's household travel survey from 2017 to determine the main drivers for ride-hailing adoption, unpack ride-hailing user characteristics, and understand how they differ from other transport users in the local context. We use findings to discuss the implications of ride-hailing for urban mobility in one of the largest cities in Latin America. Recognizing that the trajectory of adoption and development of app-based urban transport services differs from those followed in the United States and Europe, the paper hypothesizes that ride-hailing usage in a context such as Mexico may be mediated by social issues such as the perception of crime, risk of sexual harassment in public transportation, and lack of flexibility and quality in other modes. Such challenges are frequently experienced by women in this, and similar contexts as documented by the literature. [...]
Keywords: J16; N76; O32; 330; Gender; Mexico; Ride-hailing; TNC